Integrasi Nilai-Nilai Rumah Tangga Kristen dalam Kurikulum Pendidikan Agama Kristen untuk Pembentukan Karakter Kristus di Era Digital - Evi Sondag; Kezia Verena; Chanita Christie Lohy; Yeyen Darmadi; Lidiawati Lidiawati (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2025)
The growth of the digital era has a significant impact on Christian Religious Education (CRE), requiring a curriculum transformation to integrate Christian family values into academic learning. This study uses a descriptive qualitative approach with an exploratory case study design to analyze the integration of Christian family values such as love, open communication, and spiritual discipline—into the CRE curriculum. The results indicate that the integration of these values is effective in shaping students' Christlike character, encompassing cognitive, affective, and spiritual dimensions. Furthermore, technology-based learning becomes more meaningful when Christian family values are applied in the learning process. The study concludes that a curriculum model integrating these values can produce educators who are not only theologically competent but also Christlike in character, adaptable to digital developments, and responsive to the challenges of the times. This will strengthen the holistic faith formation in higher education, creating a generation that not only has a deep understanding of Christ's teachings but is also prepared to face the dynamics of life in the ever-evolving digital era.